2017
DOI: 10.1177/0741932517716899
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antecedent Exercise on Engagement During Large Group Activities for Young Children

Abstract: An antecedent exercise (AE) intervention was conducted with two young children who demonstrated challenging behaviors during a large group circle time activity in a preschool classroom; outcomes were evaluated in the context of alternating treatments designs. Results from the initial visual analysis suggested no overlap between conditions, with small, consistent effects favoring the AE condition. However, plotting reliability data suggested observer bias was present for one participant. Subsequently (post hoc)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(48 reference statements)
2
8
0
Order By: Relevance
“…For Max, CB were lower and engagement was higher during modified intervention (i.e., AE + visual schedule) compared to AE alone, indicating that a functional relation was present. These data support the findings of previous researchers that AE can yield idiosyncratic effects on subsequent behavior for preschool children (Chazin et al, 2018; Luke et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For Max, CB were lower and engagement was higher during modified intervention (i.e., AE + visual schedule) compared to AE alone, indicating that a functional relation was present. These data support the findings of previous researchers that AE can yield idiosyncratic effects on subsequent behavior for preschool children (Chazin et al, 2018; Luke et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Researchers have shown that AE can temporarily reduce a variety of CB, including stereotypy (Neely et al, 2015; Watters & Watters, 1980), aggression (Cannella-Malone et al, 2011; Conroy et al, 2008; Fite & Vitulano, 2011), out-of-seat behaviors (Celiberti et al, 1997), and inappropriate vocalizations (Yell, 1988). Additionally, researchers have demonstrated that AE can result in increased levels of academic engagement and on-task behaviors (Chazin et al, 2018; Luke et al, 2014; Mahar et al, 2006; Nicholson et al, 2011). AE might be a particularly socially valid school-based intervention, since physical activity can be conducted with small and large groups, and can be easily integrated into the context of typical classroom activities (i.e., recess, Physical Education, classroom gross motor activities).…”
mentioning
confidence: 99%
“…As frameworks for evaluating the rigor of single-case research have developed over the past decade, they generally include some form of the 80/20 rule with slight variation in the percentages. In contrast, issues with the sole use of these aggregated metrics to account for observer bias in single-case research have been thoroughly documented (Artman et al, 2012;Chazin et al, 2018;Hawkins & Dotson, 1975;Ledford & Wolery, 2013). To better account for observer bias and ensure reliability of the dependent variable, Ledford and Gast (2018) recommended that a combination of methods be employed, including using masked observers and formatively assessing reliability data.…”
Section: Discussionmentioning
confidence: 99%
“…Based on caregiver input provided throughout conditions, sequential modifications were made to the analyses (Hammond, Iwata, Rooker, Fritz, & Bloom, 2013;Kurtz, Fodstad, Huete, & Hagopian, 2013). Interobserver agreement data were collected in vivo throughout FA conditions and evaluated using formative assessment methods after each session, allowing for proactive remediation of any data collection issues (e.g., bias, observer drift, ambiguous definition, human error) prior to the completion of a child's FA (Chazin, Ledford, Barton, & Osborne, 2018).…”
Section: Discussionmentioning
confidence: 99%